Performance of serially concatenated channel coding with space time block coding in OFDM transmission systems - Muladi, Muladi; Fisal, Norsheila; Yusof, S. K. (Penerbit UTM Press, 2005)
It is well known that space-time diversity using space-time coding (STC) is an effective technique to improve wireless communication performance. STC was designed for flat fading channel and consists of space-time trellis code (STTC) and space-time block code (STBC). STTC has provided diversity gain and coding gain in the cost of decoding complexity. On the other hand, STBC only provides diversity gain but simple in decoding complexity. Thus, in this paper, we proposed serially concatenated Bose-Chauduri Hocquengheim (BCH) code with STBC from orthogonal design (STBC-OD) scheme to provide diversity gain and also coding gain in the system. We incorporated OFDM transmission system onto our proposed scheme to maintain the performance over multipath selective fading channels. Performance of the system was investigated when M-ary phase shift keying (M-PSK) modulation was used for full-rate, half-rate, and three quater-rate of transmission employing appropriate number of transmit antennas. Simulation results showed that the proposed system has improved the SNR gain over the related uncoded schemes. Channel state information was assumed available at the receiver.